METODE PEMBELAJARAN KREATIF MELALUI ALAT PERMAINAN EDUKATIF DALAM MEMBENTUK KARAKTER ANAK - Wahab, Gusnarib (Pusat Studi Gender dan Anak, IAIN Palu, 2020)
Learning is one of the activities that can be managed in education, with this discussion entitled Creative Learning Methods Through Educational Game Tools in Forming Early Childhood Character, we can make learning in education more creative so that students do not experience boredom in following the learning process given. Creative learning methods through educational play tools in shaping early childhood character, can help character formation of students in education levels ranging from kindergarten, elementary, junior high, high school and up to higher education, as for the educational game tool in question is a game tool that can be played without any burden for students and can be enjoyed by those entering the adult level. With this creative learning method through educational play tools in shaping early childhood character, it can be enjoyed when they enter adolescence and adulthood, because interesting learning will always be remembered and can be applied various kinds of learning models that can foster children's creative power, so that patterns think children are getting more advanced and modern.